POLITIK HUKUM RANCANGAN UNDANG-UNDANG CIPTA KERJA DISEKTOR LINGKUNGAN HIDUP DAN KEHUTANAN(SUATU TELAAH KRITIS) - Nugroho, Wahyu; Syahruddin, Erwin (UI Scholars Hub, 2021)
Draft Law on Cipta Kerja using the omnibus law method in the environment and forestry sector needs to be tested in the current constitutionalism of the environment. In this article, the author will focus on environmental and forestry issues in the content of the Draft Law on CiptaKerja with the formulation of the problem, how is the critical review of the material contained in the Draft Law on Cipta Kerja inthe environment and forestry sector? and what are the implications of the material content regulated in the DraftLaw on Cipta Kerja in the environment and forestry sector?The results of his research are first, the material contained in theDraft Lawon Cipta Kerjathe environment and forestry sector provides a significant change from the provisions of the law on environmentalprotection and management; secondly, Draft Law on Cipta Kerja on theenvironment and forestry sector has implications for the absence of good structuring of authority in the center-regionalrelationship over the permit and supervision system inthe environment and forestry.